Ibrahim Al-Rawi (Journal of the College of Basic Education, 2022)
Numerous studies have dealt with Iraqi military and political figures, who had a prominent role in the events of modern and contemporary Iraq, and Ibrahim Al-Rawi is considered one of those personalities who contributed to the political events of Iraq in addition to his military role in an important era marked by many military movements.